2013
DOI: 10.1080/01694243.2012.696948
|View full text |Cite
|
Sign up to set email alerts
|

Soy flour dispersibility and performance as wood adhesive

Abstract: Soy flour adhesives using polyamidoamine-epichlorohydrin (PAE) resin as the curing agent are being used commercially to make bonded wood products. The original studies on the soy-PAE adhesives used purified soy protein isolate, but the much lower cost soy flour is now used commercially. We examined the performance of commercially available soy flours that have their proteins either mainly in their native (90 protein dispersibility index (PDI)) or denatured (70 and 20 PDI) states. We expected that the more nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 15 publications
4
38
0
Order By: Relevance
“…The bonding strength of a protein adhesive depends on the interaction of the hydrophobic and hydrophilic groups of the protein with the wood material (Kumar et al 2002). Protein dispersibility index (PDI) and particle size do not influence the adhesion of soy flour adhesives to wood surfaces (Frihart and Satori 2013). Native soy proteins have a highly ordered global structure.…”
Section: Introductionmentioning
confidence: 99%
“…The bonding strength of a protein adhesive depends on the interaction of the hydrophobic and hydrophilic groups of the protein with the wood material (Kumar et al 2002). Protein dispersibility index (PDI) and particle size do not influence the adhesion of soy flour adhesives to wood surfaces (Frihart and Satori 2013). Native soy proteins have a highly ordered global structure.…”
Section: Introductionmentioning
confidence: 99%
“…Previously we had shown that phosphorylation of SF using POCl 3 at a POCl 3 -to-SF weight ratio of 0.15 (g/g) provided a PSF adhesive, designated as PSF0. 15, with a maximum wet bonding strength [13]. Briefly, a 15 % (w/w) dispersion of SF in water at pH 10.5 was stirred for 60 min at 60 °C to partially denature proteins.…”
Section: Phosphorylation Of Sfmentioning
confidence: 99%
“…An automated bond evaluation system (ABES) (Model 311c tester, Adhesive Evaluations Systems Inc., Corvallis, OR) was used to determine the bonding strength of adhesives in maple veneers [13,[15][16][17]. Maple veneers (0.8 mm thick; Columbia Forest Products, Old Fort, NC) were equilibrated at 21 °C and 50 % relative humidity for at least 24 h and cut into strips of 11.7 cm along the grain and 2 cm across the grain.…”
Section: Bonding Strength Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…To meet with the requirements on mechanical performances and water resistance, soy protein-based adhesives normally has to be modified with some cross-linkers, such as formaldehyde and its derivatives, isocyanate, epoxy, etc. [4][5][6][7][8][9]. The modification mechanism was presumed to be based on the reaction between the cross-linkers and the reactive groups from protein molecules, which including -NH 2 , -CO-NH-, -CO-NH 2 , -COOH, -OH, -SH, and -Ph-OH [10][11][12].…”
Section: Introductionmentioning
confidence: 99%